Emily Brontë and the Gothic: Female Characters in Wuthering Heights - Yukari Oda (Revue LISA)
In Wuthering Heights, Catherine can be placed in the genealogy of Gothic heroines, and the fact that the novel has been seen as an example of the Female Gothic is further evidence that the Gothic has a far-reaching influence on Wuthering Heights. It is also noticeable that Isabella and Cathy Linton resemble Gothic heroines. I do not intend to discuss these female characters as persecuted heroines. Rather, what I would like to see in this paper is how Emily Brontë received the Gothic and how her female characters are influenced by the genre. I suggest that Emily gradually makes her female characters shift into more lively figures, and Gothic heroines are transformed into several versions of more animated women in Wuthering Heights, and echo each other, mirror each other, and collaborate with one another to provide a whole view. In short, as an opposite or an incomprehensible example, each character helps others to identify themselves. They explore others to find themselves, and see others as distorted mirrors that they are not what they are. The female figures in Wuthering Heights create a whole version of women together.